Analisis Pemikiran Naquib Al-Attas tentang Integratif Sains dan Agama dalam Membangun Peradaban Pendidikan Islam - Gunagraha, Shindid; Muttaqin, Zaenal (Lembaga Yasin AlSys, 2025)
This research is motivated by the phenomenon of epistemological crises in modern science that tend to be secular and materialistic, and independent of spiritual values. This has created a disorientation in education and the development of Islamic civilization. This research aims to examine in depth the integrative concept of Syed Muhammad Naquib Al-Attas regarding the relationship between Islam and science as a solution to the dysfunction between science and religion. The method used in this study is a qualitative approach through library research, with content analysis techniques on Al-Attas's main works as well as relevant secondary literature. The results of the study show that Al-Attas rejects the dichotomy between science and religion and proposes the Islamization of science as an epistemological transformation process rooted in the principle of monotheism. Science in Islam is not neutral, but has an ethical and spiritual orientation that leads to the knowledge of God and the formation of adabi people. The conclusion of this study is that Al-Attas' thought makes a significant contribution to building an integrative, holistic, and civilized paradigm of Islamic science. Implicitly, this thinking is very relevant to develop an Islamic education system that not only produces knowledgeable people, but also moral and civilized people in facing the challenges of globalization and secularization of science.